Uso do storytelling na educação ambiental para sensibilização do público infantil sobre arraias de água doce - Corrêa, Yara Gomes (Universidade Federal do Tocantins, 2016)
Human rationality reduced its relationship with non-human animals by placing them in an object status. This fact, coupled with the urbanization process, come wearing the interrelationship between human and nonhuman animals animals throughout the generations. As an example, the relationship between humans and freshwater stingrays, has been shown in recent years in the rivers of the Amazon basin and the Tocantins-Araguaia. On the one hand, these fish are legitimated by its evolutionary and adaptive process, in their natural habitat and, secondly, humans also trampled by the need for cultural and technological development. Both enjoying the same environment, scenery set in National-TO Porto in the Tocantins River was transformed into the reservoir, due to the opening of the UHE Lajeado, Luís Eduardo Magalhães. This study aimed to be used in the storytelling environmental education to sensitize the young audience in the region, as its relationship with the freshwater stingrays. The importance of it is focused on the fact provide ways to mitigate the distorted view that has developed from the relationship between both parties, relying especially with the interdisciplinary bias. Therefore, an action research developed with the child audience of public schools located in the urban environment of the reservoir. At first, she was diagnosed prior knowledge of the target audience about the object of study; later, it has listed and scientific subsidies that might have identified the guiding principles for the development of the proposal; from there, it has prepared and produced an educational text visual material, which was verified in terms of acceptance and internalization of information, by the same children addressed initially. As a result we obtained a little story comic, which was validated by most of the target audience. As for the take-up of information it was observed that most children formulated answers that contemplated a positive relationship with the freshwater stingrays, which was not evident during the diagnostic phase. It was concluded therefore that there was effectiveness of the proposal in terms of awareness of child public and suggested to test it for the relationship with other non-human animals, which the relationship with humans can also be troubled.